Production of acetophenone C-glucosides using an engineered C-glycosyltransferase in Escherichia coli. Issue 19 (9th May 2018) - Chen, Dawei; Chen, Ridao; Xie, Kebo; Duan, Yangyang; Dai, Jungui
Graphical abstract: Highlights: An engineered whole-cell bioconversion for large-scale production of C-glucosides was developed. Eight novel acetophenone mono- and bis-C-glucosides were obtained. Mono-C-glucosides exhibited potent inhibitory effects against SGLT2. Abstract: Eight novel acetophenone mono- and bis-C-glucosides were obtained by whole cells harboring an engineered C-glycosyltransferase. Optimization of the fed-bath process improved the yield of4a to 0.97 mg/mL with 95% conversion rate, which is 2.9-fold higher than that of the single-bath. Four mono-C-glucosides (1a –4a ) exhibited potent SGLT2 inhibitory activities with IC50 values at 10 −6 M. These findings provide a cost-effective and practical synthetic strategy to produce structurally diverse and novel bioactive C-glucosides for drug discovery.